KASUS KEBAKARAN PABRIK ETANOL DI MOJOKERTO - Astanti, Aisyah (Prosiding Pendidikan Teknik Boga Busana, 2025)
The ethanol plant accident that caught fire in Mojokerto was an incident that caused significant losses and raised concerns about industrial safety. On a certain date, the plant experienced a fire that damaged facilities and caused significant environmental impacts. In the analysis of this accident, the Root Cause Analysis (RCA) method was employed to identify the underlying causes of the fire. The data was obtained from incident reports, CCTV recordings, and interviews with relevant personnel. Data analysis indicates that the fire was caused by a combination of several factors, including the failure of the fire suppression system, improper chemical management, and a lack of employee training in emergency response. By employing analytical tools such as cause-effect diagrams and 5M analysis, the root causes of the fire were successfully identified. Recommended corrective actions include maintenance of the fire suppression system, changes in chemical management, and routine training for emergency response. This research highlights the importance of conducting comprehensive RCA after industrial accidents to prevent similar incidents in the future and enhance operational safety. The proposed improvement measures can assist ethanol plants and similar industries in reducing the risk of fires and protecting both the environment and their workers.